Assessment of surgeon communication skills from the patient perspective: A national evaluation using the Communication Assessment Tool. Issue 3 (March 2022) - Armellino, Mariano F.; Marini, Pierluigi; Piazza, Diego; Manguso, Francesco; Bottino, Vincenzo; Scandroglio, Ildo; Capelli, Patrizio; Stracqualursi, Antonio; Millo, Paolo; Sarro, Giuliano; Menditto, Enrica; Makoul, Gregory; et al.
Highlights: This is the first study assessing communication skills of Italian surgeons from the patient perspective. Fewer than half of patients rated their surgeons as excellent at encouraging them to ask questions. Surgeon must devote more attention to communicating and relating with young patients. The communication skills of surgeons in the North of Italy are rated more highly than in the Center or South regions. Abstract: Objective: The Communication Assessment Tool (CAT) has previously been translated and adapted to the Italian context. This national study aimed to validate the CAT and evaluate communication skills of practicing surgeons from the patient perspective. Methods: CAT consists of 14 items associated with a 5-point scale (5 = excellent); results are reported as the percent of ''excellent'' scores. It was administered to 920 consenting outpatients aged 18–84 in 26 Italian surgical departments. Results: The largest age group was 45–64 (43.8%); 52.2% of the sample was male. Scores ranged from 44.6% to 66.6% excellent. The highest-scoring items were "Treated me with respect" (66.6%), "Gave me as much information as I wanted" (66.3%) and "Talked in terms I could understand" (66.0%); the lowest was "Encouraged me to ask questions" (44.6%). Significant differences were associated with age (18–24 year old patients exhibited the lowest scores) and geographical location (Northern Italy had the highest scores). Conclusion: CAT is a valid tool for measuring communication in surgical settings. Practice Implications: Results suggest that expectations of young people for communication in surgical settings are not being met. While there is room to improve communication skills of surgeons across Italy, patients highlighted the greatest need in the Central and Southern regions.